The ABCB Multidrug Resistance Proteins Do Not Contribute to Ivermectin Detoxification in the Colorado Potato Beetle, Leptinotarsa decemlineata (Say) - Grant Favell; Jeremy N. McNeil; Cam Donly (Insects, 2020)
The Colorado potato beetle, Leptinotarsa decemlineata (Say), is a significant agricultural pest that has developed resistance to many insecticides that are used to control it. Investigating the mechanisms of insecticide detoxification in this pest is important for ensuring its continued control, since they may be contributors to such resistance. Multidrug resistance (MDR) genes that code for the ABCB transmembrane efflux transporters are one potential source of insecticide detoxification activity that have not been thoroughly examined in L. decemlineata. In this study, we annotated the ABCB genes found in the L. decemlineata genome and then characterized the expression profiles across midgut, nerve, and Malpighian tubule tissues of the three full transporters identified. To investigate if these genes are involved in defense against the macrocyclic lactone insecticide ivermectin in this insect, each gene was silenced using RNA interference or MDR protein activity was inhibited using a chemical inhibitor, verapamil, before challenging the insects with a dose of ivermectin. Survival of the insects did not significantly change due to gene silencing or protein inhibition, suggesting that MDR transporters do not significantly contribute to defense against ivermectin in L. decemlineata.